Speech Therapy Technologies in Working with Dysarthric Children - Tasbaeva Gulbaxar Muratovna (Genius Journals, 2022)
To see if any speech and language therapy intervention aimed at improving the speech of children with dysarthria is more effective than no intervention in increasing children's speech intelligibility or communicative participation, and to compare the efficacy of different types of speech language therapy in improving children's speech intelligibility or communicative participation
Keywords: Speech; Technologies; Therapy; Dysarthric Children